Low ALT levels are associated with poor outcomes in acute coronary syndrome patients in the intensive cardiac care unit. Issue 3 (March 2022) - Segev, Amitai; Itelman, Edward; Beigel, Roy; Segal, Gad; Chernomordik, Fernando; Matetzky, Shlomi; Grupper, Avishay
Abstract: Background: Frailty is an underrecognized and important entity that bears worse prognosis. Although low serum alanine aminotransferase (ALT) can serve as a novel marker of frailty, its use was never assessed in acute coronary syndrome (ACS) patients. Methods: A retrospective analysis of hospitalized ACS patients in the intensive cardiac care unit (ICCU)between 1/5/2011 and 1/12/2020 at a single tertiary medical center. Results: The study included 3956 patients after excluding patients with ALT >40 IU/L, cirrhosis, and missing data, followed for a medianduration of 47 months (IQR 20-77).Patients were stratified into two groups based on their first ALT measurement within the index hospitalization: low-normal ALT group (ALT ≤10 IU/L) vs. high-normal ALT group (ALT >10 IU/L). Patients with ALT≤10 IU/L were older (mean age 71 years vs. 65 years, p <0.001), presented more frequently with non-ST elevation myocardial infarction (66.4% vs. 53.2%, p < 0.001), had higher rates of comorbiditiesat baseline, and had a lower Norton score upon admission. Hospitalization length was longer in the low-normal ALT group ( p < 0.001). Although the in-hospital mortality rate was similar between the groups (0.9% vs. 0.7%, p  = 0.99), long-termmortality was significantly higher in the low-normal ALT group (22.7% vs. 7.9%, p < 0.001). In a multivariate regression model ALT ≤10 IU/l was associated with increased mortality (HR 2.1, 95% CI 1.46-3). Conclusions: Lower serum ALT is associated with worse outcomes in ACS patients admitted to the ICCU. Graphical abstract: Image, graphical abstract .